(untitled) (Research, Society and Development, 2021)
In the context of the COVID-19 pandemic, inadequate spaces in terms of the dimensions of the environments and lack of flexibility for possible adjustments, not only accentuate health risks, but also interfere in the productivity of remote work and school performance. In this sense, social housing has an unsatisfactory performance in terms of functionality, mainly because they have small spaces and inadequate window frames to achieve satisfactory natural ventilation and reduce the contagion by coronavirus. The objective of this article is to analyze three single-family social housings, aiming to rethink spaces, focusing on some elements necessary to protect the health and well-being of the inhabitants. The method applied concepts of functionality and useful area, in addition to the requirements and criteria of the Brazilian bioclimatic zoning and performance standards, including the construction guidelines for single-family social housings (SH) reflecting on the need to adapt SH to guarantee well-being and inhabitants’ health. Analysis results showed that low-income buildings are precarious in terms of functionality and do not allow adaptations due to the architectural design and technical specification of walls and window frames.